2023
DOI: 10.1057/s41599-023-01960-z
|View full text |Cite
|
Sign up to set email alerts
|

Variations in racial and ethnic groups’ trust in researchers associated with willingness to participate in research

Abstract: Low enrollment in U.S. biomedical research by non-White adults has historically been attributed to mistrust, but few studies have simultaneously examined dimensions of trust in three or more racial/ethnic groups. Leveraging the racial/ethnic diversity of New Jersey, we prospectively recruited 293 adults (72% women, 38% older than 54 years of age) between October 2020 and February 2022 to complete two anonymous surveys in English or one of the common languages (e.g., Spanish, Mandarin Chinese). The first consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Previous research has shown that trust plays a critical role in effectively engaging with patients and getting them to participate in CVD trials [31]. Transparency of research strategies and potential risks significantly influence patients' willingness to take part in research [32] and female patients' trust is shaped by their perceptions of healthcare competence, empathy, communication, and autonomy [33].…”
Section: Building Trustmentioning
confidence: 99%
“…Previous research has shown that trust plays a critical role in effectively engaging with patients and getting them to participate in CVD trials [31]. Transparency of research strategies and potential risks significantly influence patients' willingness to take part in research [32] and female patients' trust is shaped by their perceptions of healthcare competence, empathy, communication, and autonomy [33].…”
Section: Building Trustmentioning
confidence: 99%